Analysis on vibration control of a large-span pedestrian suspension bridge based on a multiple tuned mass damper system. (February 2019) - Li, Zhen; Li, Dejian; Lu, Yao; Tang, Chao
Tuned mass damper is one of the commonly used passive control devices. It is the earliest used device in civil engineering control of vibration control of high-rise buildings and towering structures. For large-span pedestrian bridges, the pedestrian load spectrum covers many modalities of pedestrian bridges. It is difficult to achieve the expected results with a single tuned mass damper device. In order to obtain efficient damping, the multiple modes of a multiple tuned mass damper which may resonate under excitation are controlled. This chapter adopts the pedestrian suspension bridge over Dongtan River as the subject to arrange a multiple tuned mass damper system in the finite element model of the pedestrian suspension bridge, analyze the effectiveness of the multiple tuned mass damper system on the control of human-induced vibration of a large-span pedestrian suspension bridge, and discuss the vibration reduction effect of the multiple tuned mass damper system on the response to human-induced vibration of the pedestrian suspension bridge. The analysis shows that a multiple tuned mass damper system has a significant effect on controlling human-induced vibration of the pedestrian suspension bridge.